2018
DOI: 10.3390/met8050316
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Thixowelded AISI D2 Tool Steel

Abstract: Rigid perpetual joining of materials is one of the main demands in most of the manufacturing and assembling industries. AISI D2 cold work tool steels is commonly known as non-weldable metal that a high quality joint of this kind of material can be hardly achieved and almost impossible by conventional welding. In this study, a novel thixowelding technology was proposed for joining of AISI D2 tool steel. The effect of joining temperature, holding time and post-weld heat treatment on microstructural features and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The effects of joining temperature, holding time and post-weld heat treatment on microstructural features and mechanical properties of AISI D2 thixo-joining was reported by Mohamad et al [7]. The study showed that temperature is the most critical joining parameter to increase the joinability of the interface.…”
Section: Introductionmentioning
confidence: 85%
“…The effects of joining temperature, holding time and post-weld heat treatment on microstructural features and mechanical properties of AISI D2 thixo-joining was reported by Mohamad et al [7]. The study showed that temperature is the most critical joining parameter to increase the joinability of the interface.…”
Section: Introductionmentioning
confidence: 85%
“…Joining of materials is one of the highest demand activity in the industrial sectors [1][2][3]. The process of joining materials is known taking a lot of costs, either on its research to get the most efficient method and parameters such as pressure, temperature and welding time or in the industrial activity itself in which related to production processes.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of intensive melt stirring, non-dendritic structures may occur, with the primary α-Al phase shaped as spheroids (globular) or rosettes [5]. Non-dendritic structures exhibit rheological properties [6] improving the mechanical properties of alloys [7] and composites [8], making semisolid metal processing (SSM) [9], thixoforming [10], rheocasting [11] and thixowelding [12] unique for the production of advanced engineering parts [13]. Semisolid slurries [14] with globular solid particles may be produced by magnetohydrodynamic (MHD) [15] or mechanical stirring [16].…”
Section: Introductionmentioning
confidence: 99%